Design and Application of Portable Continuous Welded Rails Stress Homogenization Adjustment Device - HE Xianglin; LIU Ping; LU Hongyao; WU Wentao (Chengshi guidao jiaotong yanjiu)
［Objective］In order to timely and accurately grasp the internal stress distribution of continuous welded rails (CWR) and reduce the investment of manpower and material resources in CWR stress adjustment operations, it is necessary to study the issues of CWR stress adjustment. ［Method］The causes for uneven temperature distribution in CWR are introduced, and the characteristics of temperature distribution in CWR are clarified by combining infrared thermal imaging technology; a portable CWR stress homogenization adjustment device is designed and applied in actual projects. ［Result & Conclusion］The random differences in locked rail temperature, and the objective differences in meteorological parameters and materials are the reasons for the uneven temperature distribution inside CWR. On the actual operating line, there is a temperature difference at the position of adjacent fasteners, with a temperature difference of 1.8 ℃, which causes a local temperature stress extreme difference of 2.77 MPa in the steel rail. The portable CWR stress homogenization adjustment device can excite the maximum acceleration value of the rail to 305.944 m/s2, and control the longitudinal fluctuation displacement value of the rail to 0.014 mm. The CWR internal stress is thus effectively released due to the high-frequency excitation.